Cardiotoxicity induced by immune checkpoint inhibitor: The complete insight into mechanisms, monitoring, diagnosis, and treatment - Ganesh, Sridha; Zhong, Peng; Zhou, Xiaoyang (Frontiers in Cardiovascular Medicine, 2022)
Immune checkpoint inhibitors (ICIs) have been taking cancer research by storm as they provide valuable therapeutic benefits to cancer patients in terms of immunotherapy. Melanoma and non-small cell lung cancer (NSCLC) are among the most prevalent cancer varieties that were utilized in ICI trials with many other cancer types being involved too. Despite impressive clinical benefits of overall response rate (ORR), progression-free survival (PFS), etc, ICIs are also accompanied by various immune-related adverse events (irAEs). Amongst the irAEs, cardiotoxicity bags a crucial role. It is of paramount importance that ICI-induced cardiotoxicity should be studied in detail due to its high mortality rate although the prevalence rate is low. Patients with ICI cardiotoxicity can have a greatly enhanced life quality despite adverse reactions from ICI therapy if diagnosed early and treated in time. As such, this review serves to provide a complete insight into the predisposing factors, mechanism, diagnostic methods and treatment plans revolving around ICI-induced cardiotoxicity.